PERILAKU LENTUR PELAT KOMPOSIT DENGAN PENGKASARAN INTERFACE PADA MOMEN KAPASITAS LAPANGAN - Agustin Gunawan; Suprapto Siswosukarto; Bambang Supriyadi (Universitas Bengkulu, 2019)
The research aimed at investigating of the influence of surface roughing at semi-precast slab to slab strength on the first crack and the ultimate, the slab strength ratio made monolithically and composite, and to investigate crack and failure pattern of composite slab. The testing was conducted on two groups of slab which has 1:1 scales. Each group consists of three. The first group was monolith slab as control speciment. The second group was composite slab withsurface roughing. The test was conducted on two step. The first step, speciment was loaded by the repeated center static loading (10 cycle), the second step, the speciment was loaded from zero and increased step by step until speciment failed. Testing results showed that the first crack load of composite slab was approximately 14,2 % (width of 200 mm), 10,61 % (width of 400 mm), and 22,64 % (width of 600 mm) less than monolith slab. The ultimate (failure) load of composite slab was about 32,2 % (width of 200 mm), 9,8 % (width of 400 mm), and 15,9 % (width of 600 mm) less than monolith slab. The cracks occurred at slab speciment was vertical cracks extending through tensile side. The crack was indicated flexural crack, while the kind of failure type occurred at slab speciment was flexural failure.